Improvement Of Equipment Maintenance Activities At PT. Multi Star Indonesia, Tbk Based On Maintenance Management System - Ronald Nugroho Surbakti; Rosalendro Eddy Nugroho (International Journal of Economics, Business and Innovation Research, 2024)
This study aims to identify more deeply the waste that results in low productivity and quality in terms of Work Order Compliance data and Operational Breakdown Rate data from 2017 to 2021, to evaluate the implementation of lean maintenance (VSM - Value Stream Mapping) to overcome waste that results in low productivity and quality in maintenance activities through Current State Mapping and Future State Mapping with the Value Stream Mapping method approach, and to evaluate the efficiency and effectiveness of the implementation of the Improvement Maintenance Management System through the Combine & Simplify Maintenance Activities strategy through digitization. The method used in this research is Quantitative Descriptive Method. The results showed that the implementation of FSM and improvement measures in this study have proven effective in reducing waste and increasing the efficiency and productivity of maintenance activities, which is reflected in time savings and a decrease in the duration of maintenance implementation.